THE INFLUENCE OF PERCEIVED LOYALTY PROGRAM AND SATISFACTION LEVEL TOWARDS LOYALTY LEVEL OF ONLINE TRANSPORTATION CONSUMERS - Harika Tsabita; Moh. Djemdjem Djamaludin (Journal of Child, Family, and Consumer Studies, 2023)
Competition in the business of ride-hailing services has also increased along with the rapid development of technology. This study aims to analyze the effect of perceptions of loyalty programs and the level of consumer satisfaction on the level of loyalty of Grab consumers. This study used a cross sectional study design and a survey method using an online questionnaire. The analysis carried out using descriptive analysis, Spearman correlation test using SPSS 25, and the influence test using the SEM method using Smart PLS. The population of this study is Indonesian society aged 18-50 years and using Grab services more than three times in the past three months. Respondents were selected by voluntary sampling with a total of 176 respondents. The results of the study found that there was no relationship between the characteristics of respondents and the perceived loyalty program, consumer satisfaction, and consumer loyalty. The Grab loyalty program that is well perceived by consumers can increase the level of Grab consumer loyalty. Then, the increasing level of consumer satisfaction can increase the level of Grab consumer loyalty